2020
DOI: 10.1186/s12891-020-3093-z
|View full text |Cite
|
Sign up to set email alerts
|

The maximal gait speed is a simple and useful prognostic indicator for functional recovery after total hip arthroplasty

Abstract: Purpose: The present study aimed to compare the capabilities of preoperative usual and maximal gait speeds in predicting functional recovery in patients who have undergone total hip arthroplasty (THA). Methods: Primary and unilateral THAs were performed in 317 patients, and the proportion of patients who achieved unassisted walking (functional recovery) 5 days postoperatively was recorded as an outcome measure. Preoperative functional assessment included hip pain, leg muscle strength, range of motion (ROM), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The added value of the current study is that we used a cohort with unselected patients in a fast-track pathway approaching the outpatient setting. Several studies confirmed performance based measures like TUG or gait speed as independent determinants of LOS or functional recovery [ 15 , 17 , 19 , 23 , 24 ]. However, the focus in these studies was on predicting prolonged LOS or functional recovery of patients in a pathway with a mean LOS of 3–4 days.…”
Section: Discussionmentioning
confidence: 91%
“…The added value of the current study is that we used a cohort with unselected patients in a fast-track pathway approaching the outpatient setting. Several studies confirmed performance based measures like TUG or gait speed as independent determinants of LOS or functional recovery [ 15 , 17 , 19 , 23 , 24 ]. However, the focus in these studies was on predicting prolonged LOS or functional recovery of patients in a pathway with a mean LOS of 3–4 days.…”
Section: Discussionmentioning
confidence: 91%
“…Some have advocated for a definition using multiple parameters, such as low muscle strength, low muscle quantity or quality, and low physical performance [ 21 ]. Muscle performance assessment has emerged in recent years as a surrogate measure correlating with postoperative function, though there is not yet consensus regarding the optimal method [ [55] , [56] , [57] , [58] ]. Tests of gait speed or lower extremity mechanics may be indicative of poor global muscle function; however, these can be confounded by arthritis-associated pain and dysfunction of the lower extremities or mobility.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent retrospective study, gait speed is a simple and useful prognostic indicator of functional recovery in patients who have undergone joint replacement [ 35 ]. Furthermore, a longitudinal cohort study identified that orthopaedic patients’ who are discharged from hospital with slow gait speeds are more likely to develop limited functional mobility and a high risk of further adverse health events [ 36 ].…”
Section: Discussionmentioning
confidence: 99%